Lesion mimic gene HLM1 positively regulates cell death and disease resistance in rice - Zhang, Peiyun; Zong, Chaofeng; Gu, Yujie; Mei, Le; Ge, Qianwen; Liu, Pengcheng; Ma, Bojun; Chen, Xifeng (Frontiers in Plant Science, 2025)
Lesion mimic mutants are important resources for deciphering the molecular mechanism of programmed cell death (PCD) and defense response in plants. Here, we isolated a new dominant lesion mimic mutant, Hlm1, which exhibited a hypersensitive response (HR) like phenotype with excessive accumulation of reactive oxygen species (ROS) and constitutive expression of pathogenesis-related (PR) genes, displayed a spontaneous cell death and enhanced resistance to rice bacterial blight pathogens as well. Genetic analysis indicates that the lesion mimic phenotype of Hlm1 is controlled by a dominant allele, which is tightly linked to a T-DNA insertion in rice chromosome 2, and a candidate gene OsNRAT1, encoding the Nramp (natural resistance-associated macrophage protein) aluminum (Al) transporter, was found to be highly up-regulated in the Hlm1 mutant. Loss-of-function of OsNRAT1 gene by CRISPR/Cas9 in the Hlm1 mutant decreased the lesion mimic phenotype. Interestingly, OsSPL1, a validated component of rice defense responses, was identified to interact with OsNRAT1. In addition, transcriptome analysis showed that the elevated expression of OsNRAT1 in the Hlm1 mutant promotes the plant-pathogen interaction pathway and MAPK signaling pathway to activate downstream defense genes, while simultaneously inducing the production of diterpenoid phytoalexins to combat pathogen invasion. Overall, our results will enhance the understanding of the molecular mechanisms underlying programmed cell death and disease resistance in rice.